Cerebral Microcirculatory Blood Flow Dynamics During Rest and a Continuous Motor Task - Müller, Martin; Österreich, Mareike (Frontiers in Physiology, 2019)
Objectives: To examine the brain’s microcirculatory response on a continuous 5 minutes elbow movement task (EM). Methods: In 24 healthy persons (women 13, men 11, mean age ± SD, 38 ± 11years) we simultaneously recorded cerebral blood flow velocity (CBFV), changes in oxygenated/deoxygenated hemoglobin concentrations ([oxHb], [deoxHb]),, blood pressure (BP), and end-tidal CO2 over 5 minutes epochs of rest and of EM movements of the left elbow at 1 Hz. For analysis transfer function estimates of phase and gain in the low frequency range (0.07-0.15 Hz) was used. Results: ET led to a small BP increase (mean BP at rest 83 mm Hg, at ET 87; p<0.01) and a small ETCO2 decrease (at rest 44.6 mmHg, at EM 41.7 mmHg; p<0.01); it increased BP-[OxHb] phase from 55° (both sides) to 74° (right; p<0.05) / 69° left; p<0.05), and BP-[deoxHb] phase from 264°(right) / 270°(left) to 288° (right; p<0.05) / 297° (left; p=0.09). Cerebral mean transit time (mTT) of around 5.6 seconds remained unchanged. ET decreased BP-CBFV gain significantly on both sides, and BP-CBFV phase only on the right side (p= 0.05). Conclusion: EM leads to an increased time delay between BP and [OxHb] / [deoxHb] leaving cerebral mTT unchanged